The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1140/epjc/s10052-016-4092-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar interpretation of lepton spectra measured by AMS-02

Abstract: Alpha Magnetic Spectrometer (AMS-02) recently published its lepton spectra measurement. The results show that the positron fraction no longer increases above ∼200 GeV. The aim of this work is to investigate the possibility that the excess of positron fraction is due to pulsars. Nearby known pulsars from the ATNF catalog are considered to be a possible primary positron source of the high energy positrons. We find that the pulsars with age T (0.45−4.5) × 10 5 year and distance d < 0.5 kpc can explain the behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 64 publications
(164 reference statements)
5
37
0
Order By: Relevance
“…This general conclusion has also arrived at by a earlier paper [168]. Another article [169] has done a studied particularly on the pulsar interpretation of the new AMS02 data and found that any of the four pulsars they selected, or the combination of them can do the job. In the case of the multiple pulsars contribution, the positron fraction will show a particular structure at high energies.…”
Section: )supporting
confidence: 58%
See 2 more Smart Citations
“…This general conclusion has also arrived at by a earlier paper [168]. Another article [169] has done a studied particularly on the pulsar interpretation of the new AMS02 data and found that any of the four pulsars they selected, or the combination of them can do the job. In the case of the multiple pulsars contribution, the positron fraction will show a particular structure at high energies.…”
Section: )supporting
confidence: 58%
“…We can now write down the solutions for the perturbation functions in Mode 1: 169) which will serve as the initial conditions, i.e., the leading term, for the perturbation functions outside the horizon. The solutions to be obtained later that are outside the horizon and valid in the time regime that includes this initial time at the temperature T = 10 9 K will have to be matched with Eqs.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter scenario is widely adopted by some phenomenological works (Feng & Zhang 2016). It has been proposed also that in addition to the Galactic sources, the local sources may affect the CR spectra due to spectral difference between them (Kawanaka et al 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Moreover, the spectra of CR leptons with a softening behavior at ∼0.9 TeV have been measured by DAMPE [19] and HESS [20], and confirmed by CALET [21]. These exciting features have triggered models involving: (i) nearby sources [22]; (ii) pulsars [23][24][25][26][27][28]; or (iii) dark matter [29][30][31][32][33]. These models usually contain at least two free parameters.…”
Section: Introductionmentioning
confidence: 90%